Jurisprudential provisions regarding the terrorist in imami jurisprudence - Hussein ali salman; Dr.nadhir al-hasani; Dr.yasser qutaish (Journal of College of Education, 2024)
Since terrorism is the most weapon for the human soul, and it is a modern term that enemies have taken up as a means of eliminating the right doctrine py sowing discord between Islamic sects through establishing a corrupt complex that deems muslims infidels, carries out the orders of infidels, and uses the most powerful means that are forbidden rationally and legally, such as collective support, brutal killing, mutilaton, And destruction of the environment, we find that the Islamic legislator was aware of these terrorists and imposed strict criminal provisions for them, such as killing, crucifixion, cutting off hands and feet, and exile from the land. Terrorism, in this sense, has no connection to true islam, and accusing it of terrorism as a result of the legislation of jihad is a false lie, due to the difference in the powers of judgments and subjecte. And what is mentioned in the holy quran the dirivatives of the word “ruhab”a distortion of the meaning of the conventional definition of terrorism adopted by intemational law today.